2012
DOI: 10.3892/mmr.2012.890
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of infiltrating macrophages in high glucose-induced peritoneal fibrosis in rats

Abstract: Abstract. Alternatively activated macrophages (M2 macrophages) are involved in tissue remodeling and fibrosis, but their effects on peritoneal fibrosis (PF) induced by high glucose peritoneal dialysate have yet to be fully established. In this study, PF was induced in male Sprague-Dawley rats by intraperitoneal injection with Lactate-G4.25% dialysate (20 ml/rat/day) for 4 weeks. Control rats were given an intraperitoneal injection with saline. Establishment of the PF model was verified by Masson's trichrome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The M1 phenotype macrophages are induced by interferon (IFN)-γ and lipopolysaccharide (LPS). This leads to increased inducible nitric oxide synthase (iNOS), upregulation of macrophage MHC class II and CC (CC motif) chemokine receptor 7 (CCR7) expression [9]. IFN-γ, along with polarization of M1 macrophages, also promotes M1 cell expression of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL1β, IL12, and monocyte chemoattractant protein-1 (MCP-1) [10], leading to insulin resistance [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The M1 phenotype macrophages are induced by interferon (IFN)-γ and lipopolysaccharide (LPS). This leads to increased inducible nitric oxide synthase (iNOS), upregulation of macrophage MHC class II and CC (CC motif) chemokine receptor 7 (CCR7) expression [9]. IFN-γ, along with polarization of M1 macrophages, also promotes M1 cell expression of pro-inflammatory cytokines tumor necrosis factor-α (TNF-α), interleukin (IL)-6, IL1β, IL12, and monocyte chemoattractant protein-1 (MCP-1) [10], leading to insulin resistance [11].…”
Section: Introductionmentioning
confidence: 99%
“…These M2 macrophages are predominantly activated by Th2 cytokines, mainly interleukin (IL)-4 and IL-13 [9]. In non-obese subjects, adipocytes release higher levels of adiponectin that improves insulin sensitivity and enhances M2 macrophage polarization [15].…”
Section: Introductionmentioning
confidence: 99%
“…The absence of CD163 + cells among the donor GFP + cells confirmed that the recruited monocyte lineage did upregulate CD163 after infiltration into the interlobular area. CD206 (Calderon et al 2015 ; Hu et al 2012 ; Lawrence and Natoli 2011 ), CD163 (Cote et al 2013 ; Komohara et al 2006 ; Polfliet et al 2006 ), and arginase 1 (Lawrence and Natoli 2011 ) are all M2 macrophage markers, indicating that the recruited monocytes polarized to the M2 phenotype in that location.…”
Section: Discussionmentioning
confidence: 99%
“…As for IL-4-producing cells, innate cells such as eosinophils and mast cells are reported to produce this cytokine (Loke et al 2007 ). These cells are abundant in the peritoneal cavity, and inflammation of the peritoneal organs including the pancreas may well stimulate IL-4 secretion by these cells (Hu et al 2012 ). This cytokine might have penetrated the serosa covering the pancreas and polarized macrophages in the interlobular area to M2 phenotype in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation